THE ROLE OF MATHEMATICAL LITERACY FOR FUTURE SPECIALISTS IN THE FIELD OF SOFTWARE ENGINEERING - Вакуленко, Алла (SWorldJournal, 2023)
The article examines the essence of the concept of "mathematical literacy", its role for the successful professional activity of future specialists in the "Software Engineering" specialty, substantiated meaningful components of the process of forming mat